PLATELET LEUCOCYTE AGGREGATES ANALYSIS IN LEUCODEPLETED AND NON-LEUCODEPLETED PLATELET CONCENTRATES - Teguh Triyono; Raehanul Bahraen (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Activated platelet could initiate aggregation and linkage with nearby leucocytes to form Platelet-Leucocyte Aggregates (PLA). Leucodepletion procedure could remove leucocyte and separate it from the other blood components therefore minimalizing the probability of PLA formation. We analyze percentage difference of PLA in leucodepleted and non-leucodepleted platelet concentrate. Dual expression of CD41 and CD45 was determined by flowcytometry method representing the value of PLA, PLA percentage of each group was calculated and analyzed with statistical software SPSS 22. Mean percentage value of PLA in leucodepleted group was 63.05 ±19.86, meanwhile in non-leucodepleted group was 64.61 ±17.27. We found that the percentage of PLA in nonleucodepleted group is higher than leucodepleted although the difference is not statistically significant.